Analysis of health care costs for patients with cancer at the end of life: Hospital versus home with palliative care, at the third level of care - Amado-Tineo, José Percy (2022)
Background: The final stage of cancer patients generates high costs, especially in hospitals. Objectives: To determine the difference in care costs at the end of life for cancer patients in the hospital versus at home. Material and methods: Retrospective cost analysis study in patients who died of clinical stage IV cancer in a tertiary social security hospital, March 2018. A home group (Home) of a palliative program was compared with a hospital group (Hospital) admitted from the emergency department. Direct costs of professional services, hospitalization, procedures, auxiliary exams, and medications were estimated. Chi square and Student's T were used for statistical analysis, considering a value of p<0.05 and using SPSS 24.0. Results: 81 patients in Home and 22 in Hospital were included, aged between 36 and 96 years, with a median of 72 years in Home and 77 in Hospital (p=0.97), female sex 59 and 73% respectively (p= 0.25), predominantly cancer of digestive and genitourinary origin. The average cost per patient in Home was 497 US dollars and in Hospital 1908 (p<0.01), with a daily average per patient of 17 vs 447 respectively. In the Hospital, the costs of hospitalization, auxiliary tests (tomography, resonance, arterial gas analysis, C-reactive protein) and antibiotics (ertapenem and colistin) predominated, while in the Home the highest cost was in medical services and medications. Conclusion: The medical costs in the final stage of life of patients with advanced cancer are 3.8 times higher when they die in the hospital than at home.